P09.03 Treatment of mycoplasma genitalium with azithromycin 1 g is less efficacious and associated with induction of macrolide resistance compared to a 5-day regimen. (13th September 2015) - Horner, P; Ingle, S; Garrett, F; Blee, K; Kong, FYS; Moi, H
Abstract : Introduction: Mycoplasma genitalium (MG) is an emerging important STI. Failure rates with azithromycin 1 g appear to be increasing. This may be due to the emergence of macrolide antimicrobial resistance as a consequence of extensive use of azithromycin 1 g. An extended regimen of azithromycin 500 mgs on day one then 250 mgs daily for 4 days (5 day regimen) was introduced in the 1990s for treatment of MG and has high efficacy rates (if no pre-existing macrolide resistance) and is less associated with induction of macrolide resistance. There are no comparative trials of the two regimens. We undertook a meta-analysis of MG treatment studies using the two azithromycin regimens to determine which is more effective. Methods: Medline was used to identify published articles including the search terms Mycoplasma genitalium and resistance up to March 2015. Treatment studies using azithromycin 1 g or 5 days were identified in which patients were initially assessed for macrolide resistance genetic mutations, and those who failed were again resistance genotyped were selected. Sensitivity analyses included only patients without prior treatment. Results: Six studies were identified totaling 424 patients of whom 78 (18.4%) had received the 5 dy regimen. Only one person failed the 5 day regimen and no resistance was detected. Compared to the 5 day regimen, azithromycin 1 g had a higher risk of failure (difference: 12.9%, 95% CI: 8.4%, 17.3%) and more developed macrolide resistance (risk difference: 12.1% (8.7%, 15.6%). The 5 day regimen included 52 patients with prior doxycycline treatment when these were excluded sensitivity analysis showed a failure risk difference of 10.3% (2.1%, 18.6%). Resistance risk did not change. Conclusion: Azithromycin 1 g is more likely to result in treatment failure and the development of macrolide antimicrobial resistance than 500 mgs on day one then 250 mgs daily for 4 days. Disclosure of interest statement: PH: - Has received funding for providing expert advice on M. genitalium diagnostics. HM – has received a honorarium and travel expenses from Becton Dickinson for a lecture on Mycoplasma genitalium . SI, FG, FK and KB – none to declare.